A Low Psoas Muscle Index before Treatment Can Predict a Poorer Prognosis in Advanced Bladder Cancer Patients Who Receive Gemcitabine and Nedaplatin Therapy. (13th April 2017) - Kasahara, Ryo; Kawahara, Takashi; Ohtake, Shinji; Saitoh, Yoko; Tsutsumi, Sohgo; Teranishi, Jun-ichi; Miyoshi, Yasuhide; Nakaigawa, Noboru; Yao, Masahiro; Kobayashi, Kazuki; Uemura, Hiroji
Abstract : Introduction . Gemcitabine and cisplatin (GC) is a gold-standard first-line systemic chemotherapy for advanced urothelial carcinoma (UC). However, it may cause severe adverse effects such as renal toxicity, gastrointestinal toxicity, and neurotoxicity. Sarcopenia is the age-related loss of skeletal muscle mass. A correlation between sarcopenia and the oncological prognosis has been reported. In UC, several studies have noted that patients with sarcopenia had a greater incidence of complications and worse survival after radical cystectomy or chemotherapy. Our institute introduced gemcitabine and nedaplatin (GN) for UC patients with renal failure. We investigated whether the presence of sarcopenia predicted the prognosis of patients with advanced UC who were treated by GN chemotherapy. Methods . A total of 27 patients (male, n = 21 ; female, n = 6 ) received GN therapy for metastatic UC from 2005 to 2016. The institutional review board of Yokohama City University Hospital approved this study. The psoas muscle index (PMI, cm 2 /m 2 ) was calculated using this formula: right psoas muscle area (cm 2 )/the square of the body height (m 2 ). The overall survival (OS) of the high PMI group (male: ≥2.49, female: ≥2.07) and low PMI group (male: <2.49, female: <2.07) was compared. Results . Kaplan-Meier survival curves and a log-rank test revealed that the high PMI group had significantly better OS than the low PMI group (p = 0.015 ). The mean survival of the high and low PMI groups was 561 days and 223 days, respectively. Conclusions . In the present study, we revealed that sarcopenia (a low psoas muscle volume) might be a predictive factor for poorer overall survival in patients with advanced urothelial carcinoma who are undergoing GN chemotherapy.